2009
DOI: 10.17221/1074-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Understanding of the Chemical Reactions Responsible for Bread Flavour Quality

Abstract: This work aimed at analysing bread extracts obtained under headspace and artificial mouth conditions in order to study the reactions responsible for bread flavour quality. Selected extraction conditions were first compared according to the odour and aroma representativeness of the bread extracts. The optimal conditions were then applied to extract volatiles of a conventional gluten bread formulation and an innovative gluten-free bread formulation. Results reveal that an extraction duration of 10 min in the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
(11 reference statements)
0
9
0
1
Order By: Relevance
“…Similarly, a high number of volatile compounds identified were originated by lipid oxidation, which was related to the presence of shortening in the formulation. Poinot and others () identified higher quantity of compounds from lipid oxidation in gluten‐free bread than in wheat bread due to the oil content in the formulation. Marie and others () observed that lipid oxidation occurs principally during dough preparation and depends on fatty acids type and content and on the presence of antioxidants on raw matter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a high number of volatile compounds identified were originated by lipid oxidation, which was related to the presence of shortening in the formulation. Poinot and others () identified higher quantity of compounds from lipid oxidation in gluten‐free bread than in wheat bread due to the oil content in the formulation. Marie and others () observed that lipid oxidation occurs principally during dough preparation and depends on fatty acids type and content and on the presence of antioxidants on raw matter.…”
Section: Resultsmentioning
confidence: 99%
“…Sensory properties as well as physical characteristics of different gluten‐free breads have been widely investigated. However, only Poinot and others () has studied volatile compounds of gluten‐free bread. Bread formulation, as well as the modification of bread‐making process can influence volatile compounds released from bread which, in turn, affect to overall odorant perception (Poinot and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the articles regarding bread aroma and, concretely, the few articles regarding gluten‐free bread aroma have employed gas chromatography/mass spectrometry (GC‐MS) as the analytical technique for the determination or quantification of volatile compounds regardless the sample treatment. Proton transfer reaction/mass spectrometry (PTR‐MS) could represent a suitable alternative to the use of GC‐MS for the determination of volatile compounds because GC protocols are usually lengthy and time consuming .…”
Section: Introductionmentioning
confidence: 99%
“…The differences in proteins, sugars, lipids, enzymes and antioxidants between the different gluten-free flours/ starches could lead to important differences in the volatile profile of gluten free breads. Until now, research in gluten-free bread aroma has been focused on the understanding of the origin of the volatile compounds compared to wheat bread (Poinot et al 2009). There are also a few articles regarding the improvement of gluten-free bread aroma based on the method of baking (Aguilar et al 2015) or on the addition of sugar-amino acid pairs to encourage Maillard reaction (Pacyński et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, as far as we know, there have not been studies of the influence on gluten-free bread aroma of different flours or starches. All the reported articles refer to a mixture of gluten-free flours [rice, corn and buckwheat flours with corn and potato starches (Poinot et al 2009) or corn starch with chickpea flour (Aguilar et al 2015)] or to a commercial preparation based on starches (Pacyński et al 2015).…”
Section: Introductionmentioning
confidence: 99%